Dampak Pemanfaatan Teknologi SEO dalam Pengembangan Website Promosi untuk Meningkatkan Visibilitas UMKM Pariwisata - Sulistianingsih, Indri; Ade Rizka; Virdyra Tasril; Donny Sanjaya; Rama Prameswara Ritonga (JPM: Jurnal Pengabdian Masyarakat, 2025)
Digital technology development offers significant opportunities for tourism SMEs to increase their visibility and marketing reach. However, limited knowledge and practical implementation of digital marketing, especially SEO (Search Engine Optimization), remain major obstacles for tourism SMEs in Bali. This community service program aims to enhance the online visibility of Explore Tour and Travel Bali SME through the development of an SEO-optimized website and improvement of the SME team's digital capabilities. The community service partner is Explore Tour and Travel Bali SME, which operates in tour guide services and travel packages targeting both domestic and international tourists. The implementation method uses a participatory approach through five stages: (1) preparation, including problem identification and needs analysis; (2) SEO strategy planning and website content design; (3) website implementation and on-page and off-page SEO optimization accompanied by SME team training; (4) website performance evaluation and team capability assessment; and (5) sustainable development through periodic mentoring. Results show significant improvements with organic website traffic increasing by 42%, 8 keywords ranking on Google's first page, and SME revenue growing by 27% within 6 months of implementation. Positive changes were also observed in attitude aspects (78% increase in digital literacy), socio-cultural aspects (business process transformation from conventional to digital), and economic aspects (market diversification and marketing cost efficiency). This program demonstrates the effectiveness of implementing an SEO-optimized website as a strategy for enhancing visibility and sustainability of SMEs in the tourism sector.